2016
DOI: 10.5194/nhess-16-15-2016
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and validation of FLFA<sub>rs</sub> -- a new flood loss function for Australian residential structures

Abstract: Abstract. Rapid urbanisation, climate change and unsustainable developments are increasing the risk of floods. Flood is a frequent natural hazard that has significant financial consequences for Australia. The emergency response system in Australia is very successful and has saved many lives over the years. However, the preparedness for natural disaster impacts in terms of loss reduction and damage mitigation has been less successful.In this paper, a newly derived flood loss function for Australian residential … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Figure 6. Comparison of the flood damage estimation models' precision per water-depth class (RMSE: root mean square error; number of samples for each sub-class of water depth, respectively, is 14, 36, 52, 96, 125, 222, and 68). of study (Hasanzadeh Nafari et al, 2016b;McBean et al, 1986).…”
Section: Results Comparison and Model Validationmentioning
confidence: 97%
See 2 more Smart Citations
“…Figure 6. Comparison of the flood damage estimation models' precision per water-depth class (RMSE: root mean square error; number of samples for each sub-class of water depth, respectively, is 14, 36, 52, 96, 125, 222, and 68). of study (Hasanzadeh Nafari et al, 2016b;McBean et al, 1986).…”
Section: Results Comparison and Model Validationmentioning
confidence: 97%
“…r and D max , respectively), with reference to the empirical dataset (Hasanzadeh Nafari et al, 2016a). The selection will be made by the chi-square test of goodness of fit to minimize predictive errors.…”
Section: Calibration Of Flf-itmentioning
confidence: 99%
See 1 more Smart Citation
“…The Flood Loss Function for Australian residential structures (FLFA rs ) was newly developed by Hasanzadeh Nafari et al (2016b). The FLFA rs is an empirical-synthetic model, meaning that this model was initially developed using a simplified synthetic approach called the sub-assembly method, developed by the HAZUS manual (FEMA 2012).…”
Section: Flfa Rsmentioning
confidence: 99%
“…In order to reduce the uncertainty problems. In the last years, some applications of this method to flood risk have been performed (see Merz et al, 2013;Chinh et al, 2016;Hasanzadeh Nafari et al, 2016Kreibich et al, 2017;Spekkers et al, 2014), but literature in this field is still scarce if compared to the numerous studies that use simpler uni-variable models. Nevertheless, Merz et al (2013) demonstrated that tree based models are able to improve the performance of existing models like stage-damage functions and to better identify the most informative independent variables and their interactions (e.g., they can identify different importance 25 levels of a same variable, depending on the value of another variable).…”
mentioning
confidence: 99%